Multi‐unit building address geocoding: An approach without indoor location reference data. Issue 1 (21st January 2023) - Nottrot, Bas; Folmer, Erwin; Roy, Debraj; Scheer, Bob; Merx, Peter
Abstract: Accurately mapped locations within multi‐unit properties are useful for several organizations in today's society. Published work on geocoding methods either require detailed location reference data or does not apply to multi‐unit buildings. In this research, a generalizable method is realized to map apartment addresses to their explicit locations without access to indoor location reference data based on publicly available address‐ and geospatial‐building information. The performance of this approach is measured by conducting a comparative study between a linear interpolation baseline and gradient‐boosted decision trees model. The proposed method can successfully geocode addresses across different building shapes and sizes. Furthermore, the model significantly outperforms the baseline in terms of positional accuracy proving the feasibility of approximating apartment locations by their address‐ and geospatial‐building information.